Analog Configurability-Test Scheme for an Embedded Op-Amp Module in TI MSP430 Microcontrollers - Laprovitta, Agustín (2013)
This paper proposes the application of the analog configurability test (ACT) approach for an embedded analog configurable circuit, composed by operational amplifiers and interconnection resources that are embedded in the MSP430xG461x microcontrollers family, with the aim of verifying its mode programmability. This test strategy is particularly useful for applications involving in-field circuit reconfiguration, and require reliability and safe operation characteristics. The approach minimizes the cost in hardware overhead by employing only the hardware and software resources of the microcontroller. An embedded test routine sequentially programs selected module configurations, sets the test stimulus, acquires data from the internal ADC, and performs required calculations to determine the gain of the block. The test approach is experimentally evaluated using an embedded-system based real application board. Our experimental results show very good repeatability, with very low errors. These results show that the ACT proposed here is useful for testing the functionality of the EACC under test in a real application context by using a simple strategy at a very low cost.